A Design of Agricultural Greenhouse Monitoring System using Iot (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
This article describes the work of IOT based wireless device network for observing atmospheric phenomenon, warming, and industrial pollution at various intervals of a greenhouse setting. The wireless device networks mechanically monitors the environmental parameters within a greenhouse and initiates the management measures to be taken. The mechanism checks the environmental conditions and if the worth exceeds intensity a message is sent. The image process techniques are used to detect and eradicates the pests. With the assistance of substances motors the mechanism will move round the inexperienced house on wheels.For input we have considered four main parameters of the plant such as Illumination, Temperature, Soil Moisture and Humidity. Men made errors are rectified by using automated set up system. IOT is the best supporting technology for developing automated set up mode.